Effect Of White Rot Fungi Variation On The Biopulping Of Oil Palm Trunk - Pooja, Singh (2014)

(untitled)
Lignocelluloses biomass is an important and sustainable natural resource for paper making. Wood the predominant source consists of flexible cellulose fibres, its pretreatment makes cellulose more accessible to enzymatic hydrolysis by modification of the lignin.Biological pulping is the treatment of lignocellulosic materials with oxidative lignin-degrading white rot fungi prior to pulping process. Biojisim lignoselulosik adalah suatu sumber semulajadi yang penting dan berterusan bagi pembuatan kertas. Kayu merupakan sumber utama yang mengandungi gentian selulosa yang fleksibel, pra rawatan menghasilkan selulosa yang lebih cenderung untuk hidrolisis berenzim melalui pengubahsuaian penghalang lignin.